2007
DOI: 10.3155/1047-3289.57.10.1200
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Source Apportionment of Urban Particulate Matter to Uncertainty in Motor Vehicle Emissions Profiles

Abstract: A sensitivity analysis was conducted to characterize sources of uncertainty in results of a molecular marker source apportionment model of ambient particulate matter using mobile source emissions profiles obtained as part of the Gasoline/Diesel PM Split Study. A chemical mass balance (CMB) model was used to determine source contributions to samples of fine particulate matter (PM2.5) collected over 3 weeks at two sites in the Los Angeles area in July 2001. The ambient samples were composited for organic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 1 publication
0
29
0
Order By: Relevance
“…In fact, both indeno[cd]pyrene and benzo [ghi]perylene have been used in organic molecular marker-chemical mass balance models (MM-CMB) to apportion the contribution of gasolinepowered motor vehicle exhaust to atmospheric particulate organic carbon (Chow et al, 2007;Sheesley et al, 2007). Figure S1 (http://www.atmos-chem-phys.net/9/3347/ 2009/acp-9-3347-2009-supplement.pdf) illustrates that the PAH/OC ratio for benzo [ghi]perylene, in particular, is much higher for the two gasoline-powered motor vehicle exhaust average profiles (Lough et al, 2007;Rogge et al, 1993) in comparison to the same ratio for wood smoke emission profiles (Lee et al, 2005;Schauer et al, 2001;Fine et al, 2002Fine et al, , 2004 and reported diesel-powered motor vehicle exhaust (Rogge et al, 1993;Lough et al, 2007;Riddle et al, 2007). A further exploration of the apportionment of OC based on published PAH/OC ratios for motor vehicle exhaust is included in the Supplementary Material.…”
Section: Fraction Biomass and Molecular Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, both indeno[cd]pyrene and benzo [ghi]perylene have been used in organic molecular marker-chemical mass balance models (MM-CMB) to apportion the contribution of gasolinepowered motor vehicle exhaust to atmospheric particulate organic carbon (Chow et al, 2007;Sheesley et al, 2007). Figure S1 (http://www.atmos-chem-phys.net/9/3347/ 2009/acp-9-3347-2009-supplement.pdf) illustrates that the PAH/OC ratio for benzo [ghi]perylene, in particular, is much higher for the two gasoline-powered motor vehicle exhaust average profiles (Lough et al, 2007;Rogge et al, 1993) in comparison to the same ratio for wood smoke emission profiles (Lee et al, 2005;Schauer et al, 2001;Fine et al, 2002Fine et al, , 2004 and reported diesel-powered motor vehicle exhaust (Rogge et al, 1993;Lough et al, 2007;Riddle et al, 2007). A further exploration of the apportionment of OC based on published PAH/OC ratios for motor vehicle exhaust is included in the Supplementary Material.…”
Section: Fraction Biomass and Molecular Weightmentioning
confidence: 99%
“…Specific PAHs may be more valuable as molecular markers than others in source apportionment models for OC when used in conjunction with more unique tracers such as hopanes and levoglucosan (Chow et al, 2007;Jaeckels et al, 2007;Lough and Schauer, 2007). However, more investigation into the sources of individual atmospheric PAHs is warranted to inform current source apportionment techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties that are either too lenient or to stringent can have a significant effect on the PMF analysis outcome. [222][223][224] Finally, it should be pointed out that CMB and PMF analyses have been highlighted in this review because these are the two most commonly used source apportionment tools. However, they are certainly not the only tools and there will be a wide variety of uses of organic marker data in may applications in the future.…”
Section: Comparison Of Cmb and Pmf Sourcementioning
confidence: 99%
“…It should be noted that some uncertainty in the apportionment of OC to primary sources exists due to the sensitivity of CMB to the type and composition of source profiles used (Subramanian et al 2006;Lee and Russell 2007;Lough and Schauer 2007;Rutter et al 2008). Relevant to the work presented here, Sheesley et al (2007) demonstrated that although the apportionment of OC to biomass burning by CMB is sensitive to the choice of source profile (the reported standard deviation across 5 source profiles was a little greater than 30%), the uncertainty due to the choice of profile is similar to the underlying analytical uncertainty of the levoglucosan measurements, providing confidence in the apportionment of OC to biomass burning.…”
Section: Chemical Mass Balance (Cmb) Sourcementioning
confidence: 99%